Microcephalin and pericentrin regulate mitotic entry via centrosome-associated Chk1 - Tibelius, A; Marhold, J; Zentgraf, H; Heilig, C.E; Neitzel, H; Ducommun, B; Rauch, A; Ho, Anthony; Bártek, Jiří; Kramer, A (The Journal of cell biology, 2009)
Primary microcephaly, Seckel syndrome, and microcephalic osteodysplastic primordial dwarfism type II (MOPD II) are disorders exhibiting marked microcephaly, with small brain sizes reflecting reduced neuron production during fetal life. Although primary microcephaly can be caused by mutations in microcephalin (MCPH1), cells from patients with Seckel syndrome and MOPD II harbor mutations in ataxia telangiectasia and Rad3 related (ATR) or pericentrin (PCNT), leading to disturbed ATR signaling. In this study, we show that a lack of MCPH1 or PCNT results in a loss of Chk1 from centrosomes with subsequently deregulated activation of centrosomal cyclin B-Cdk1.
Keywords: aktivace enzymů; Animals; Microcephaly; buněčné linie; Enzyme Activation; mikrocefalie; centrozom; lidé; fosfatasy cdc25; antigeny; Antigens; proteinkinasy; Mitosis; proteiny nervové tkáně; Cell Line; mitóza; cyklin B; Nerve Tissue Proteins; Centrosome; Cyclin B; cdc25 Phosphatases; RNA Interference; Protein Kinases; zvířata; RNA interference; Humans